Nanomaterials in recycled aggregates concrete applications: mechanical properties and durability. A review - Allujami, Hamzeh Marwan; Abdulkareem, Muyideen; Jassam, Taha M.; Al-Mansob, Ramez A.; Jing, Lin Ng; Ibrahim, Azmi (Cogent OA, 2022)
The use of recycled aggregates concrete (RAC) contributes effectively to reduce CO2 emissions from concrete manufacturing process while also protecting natural resources by utilizing existing available concrete as an aggregates source for a new one. Studies on the behaviour of RAC have revealed negative effects on concrete strength and microstructure development, resulting in deterioration of mechanical and durability properties. As a result, numerous practical studies have been implemented to enhance the RAC properties using various treatment techniques such as chemical, physical and heating treatments. However, most of these techniques are ineffective compared to conventional concrete applications due to poor mechanical performance of RAC, insufficient environmental requirements, and prolonged treatment times. Recently, the use of nanomaterials has been given significant concern in RAC research. Their nano-sized particles can help to reduce micropores formation by acting as a filling agent to produce a high-density microstructure, thereby enhancing the mechanical properties and durability of RAC. This had led to a wide range of studies being published on improving RAC properties by using nanomaterials. However, relatively few literatures had been conducted on the effects of different types of nanomaterials on the performance of RAC exposed to various types of loads and various external environmental impacts. Besides, the conditions used by authors in these literatures limit comparisons, and in some cases contradictory findings are observed. Thus, this paper aims to bridge the knowledge gap between researchers. This would allow the potential of nanotechnology in innovations to be applied in appropriate areas of RAC applications to benefit the general public good. This paper aims to provide a critical review and comprehensive conclusions on the performance of nano-modified RAC under external loads, environmental impacts and other various conditions. The effects of nanomaterials on the compressive, tensile, and flexural strength of RAC are discussed. The nanomaterials considered are nano-SiO2, nano-CaCO3, nano-TiO2, nano-Clay, nano-Al2O3, and nano-Carbon. Durability characteristics including water absorption, chloride penetration, fire exposure, abrasion resistance, acid and carbonation diffusions are extensively discussed. Microstructure characteristics using SEM, XRD, EDS, and micro-hardness of nano-modified RAC are addressed as well.